2008
DOI: 10.1016/j.ejcts.2008.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bedside entertainment services’ effect on post cardiac surgery physical activity: a prospective, randomised clinical trial

Abstract: We have demonstrated that the bedside entertainment systems may have an adverse effect on post cardiac surgery patient ambulation and may contribute to an increase in hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…In our study, most of the participants engaged in bedside entertainment (the hospital provided Internet and television). This finding was similar to the result reported in previous studies (Dodge et al 2008, Karjalainen et al 2008, Papaspyros et al 2008, Bier et al 2009, Couture et al 2010, Li et al 2010a, O'Sullivan & Chard 2010. Enabling participants to maintain contact via the Internet with their families who were living far away was especially important as social support plays a critical role in rehabilitation, such as provides sense of encouragement, care and connection (Reed et al 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, most of the participants engaged in bedside entertainment (the hospital provided Internet and television). This finding was similar to the result reported in previous studies (Dodge et al 2008, Karjalainen et al 2008, Papaspyros et al 2008, Bier et al 2009, Couture et al 2010, Li et al 2010a, O'Sullivan & Chard 2010. Enabling participants to maintain contact via the Internet with their families who were living far away was especially important as social support plays a critical role in rehabilitation, such as provides sense of encouragement, care and connection (Reed et al 2010).…”
Section: Discussionsupporting
confidence: 87%
“…A few studies discussed leisure for patients in hospital. Papaspyros et al (2008) studied entertainment services at the bedside of patients with cardiac surgery using a randomised clinical trial and reported that bedside entertainment including net surfing, taking phone calls, sending e-mail, watching television and listen to the radio; gaming affected the ambulation of patients after cardiac surgery, contributing to a longer stay in hospital. One study in Finland explored school-age children's experience in hospital and suggested that leisure could reduce their worries and fears, in turn benefitting pain management (Pelander & Leino-Kilpi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one can justify, in our study, the significant negative correlation of the 6-MWT distance walked by the patient with the time of hospital stay, because it suggests that the patient who presents more deambulation ability has a functional capacity more suitable for hospital discharge, reflecting better the functionality than the lung function alone. The significant correlation of FVC and FEV 1 with the 6-MWT also suggests that deambulation ability may better reflect overall functional capacity and can be justified by the fact that greater deambulation capacity is associated with higher stimulation of ventilation, increased pulmonary perfusion and detachment of secretions and oxygenation improvement [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that immobility post cardiac surgery contributes to an increased risk of postoperative complications and an increased hospital stay [5, 6]. However, not much is known about the influence of the preoperative PA status on the postoperative outcome after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%